The analysis of the causes of protein precipitate formation in the blanched soymilk. (1st March 2017) - Wang, Yahui; Xing, Jiyun; Wang, Ruican; Guo, Shuntang
Highlights: Blanching increased protein precipitates both before and after heating soymilk. Blanching made denaturated 7S in soybean form particles or larger aggregation. Aggregated 7S caused by blanching cannot hinder the growth of protein aggregation. Abstract: This paper explored the causes of protein precipitate formation in blanched soymilk prepared by blanching soybeans through studying the changes in composition and amount of protein particles during its thermal processing. Compared with the traditional method of preparing soymilk, blanching changed the thermal aggregation behavior of protein particles. Results showed that when blanching was applied to soybeans, β-conglycinin (7S) was denatured in the blanched soybeans, which resulted in the fixation and aggregation of 7S prior to the grinding processing. Therefore, 7S lost its inhibitory ability on the growth of other protein aggregation, explaining the increased insoluble precipitates in the blanched soymilk.